Potassium supply mechanisms and its absorption efficiency in soybean, maize, pearl millet, rapeseed and lablab - Costa, Newton de Lucena; Filho, Germano Nunes Silva; Sena, José Ozinaldo Alves de; Rodrigues, Antônio Neri Azevedo; Anghinoni, Ibanor (Pesquisa Agropecuaria Brasileira, 2014)
The evaluation of soil nutrient availability for the plants through chemical methods presents limitations, because morpho-physiological parameters of the plant are not considered. With the objective to evaluate the contribution of potassium supply mechanisms and its absorption efficiency in soybean (Glycine max (L.) Merrill), maize (Zea mays L.), pearl millet (Pennisetum americanum (L.) Leek), rapeseed (Brassica campestris L.) and lablab (Lab-lab purpureus (L.) Sweet), a greenhouse experiment was conducted at Faculdade de Agronomia of Federal University of Rio Grande do Sul State, Brazil, using a Structural Red Soil Similar Disthrophic - Hapludults. The supply mechanisms contributions were affected (P <0.05) in each studied specie. The diffusion proved to be the main potassium supply mechanism for all the species. Root interception was the most important for maize and soybean, because these species presented, relative to others, the largest root volumes. Mass flow was prominant for soybean, lablab and rapeseed, due to the high transpiration coefficients. Rapeseed was the most efficient in potassium absorption, followed by maize, pearl millet and lablab, although maize, lablab and soybean showed higher ability in potassium accumulation. Soybean, lablab and pearl millet were more efficient in absorbed potassium utilization, presenting the smallest absorbed potassium/produced dry matter ratio.